Homing in rocky intertidal fish. Are Lipophrys pholis L. able to perform true navigation? - Jorge, Paulo (2013)
Although navigation is common in many animals, only a few perform true navigation, meaning that they have the ability to return to a given place by relying on indirect cues obtained at the release site (i.e., by relying on information from a ‘‘map and compass’’ mechanism). The common intertidal fish, Lipophrys pholis, is thought to have homing abilities through a mechanism that primarily makes use of familiar landmarks (i.e., piloting). Anecdotal reports that individuals return to their home pools after release at unfamiliar sites suggest that L. pholis might use cues collected at the release site to find their way back (i.e., they might use map and compass information). Using a completely artificial setup, we tested the homing abilities of L. pholis as a function of age, sex, and familiarity with the release site. The findings showed that motivation for homing is present only in the adult phase and is independent of sex and/or familiarity with the release site. Moreover, adults released at a completely unfamiliar place oriented themselves in a direction roughly similar to that of their home pools. The fact that L. pholis were tested in a complete artificial environment means that hydrodynamic cues can be excluded as playing a role in this process and restricts the candidate options (e.g., magnetic cues). The ability to perform navigation based on a ‘‘map and compass’’ mechanism raises many interesting questions about the learning process, once these individuals have restricted home ranges during their lives. In vertebrate navigation, the cues used during the navigation process are a question of debate, and L. pholis offers an outstanding model to test hypotheses and ultimately provide answers.